Enhancing Governance through IPSAS: Impacts on Transparency and Accountability in Public Sector Financial Reporting - Rochman Marota; Razana Juhaida Johari (Jurnal Ilmiah Akuntansi, 2024)
This study addresses the empirical gap in understanding the practical challenges and long-term impacts of implementing International Public Sector Accounting Standards (IPSAS) on public trust and policymaking efficiency in the public sector. It explores the impact of IPSAS on transparency and accountability in financial reporting, assessing how adoption influences the comparability and reliability of financial statements, public trust, and governance quality. Using a qualitative approach, the research reviews literature and case studies across various jurisdictions to evaluate the transition to standardized accounting practices. Findings indicate that IPSAS significantly enhances transparency and accountability, reduces information asymmetry, and improves oversight and decision-making in budget management. However, challenges such as the need for extensive training, system upgrades, and local context adaptation persist. The study emphasizes the importance of capacity building and technological investment to maximize IPSAS benefits, providing insights for policymakers and public sector managers on improving governance and financial reporting. Despite focusing on conceptual analysis and lacking longitudinal data, this research paves the way for future studies on the enduring effects of IPSAS and best practices in public sector accounting.